Posmodernidad y subjetividad. Una interpretación de la propuesta de Sousa Santos según la crítica de Habermas a la posmodernidad - Galé Argudo, Miguel J. (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this essay we want to remark the features about what by Sousa Santos is called “post-modern critical theory”. This conception faces with the so called “modern critical theory” and engages with Foucault´s heritage. This conception will be crityzed according to other perspectives (v. g. Habermas) disagreed with posmodernity hits like unmasking subjectivity or reducing social action to power action.